A GIS-based framework for addressing conflicting objectives in the context of an ecosystem approach to fisheries management—a case study of the Portuguese sardine fishery. (31st July 2018) - Szalaj, D; Wise, L; Rodríguez-Climent, S; Angélico, M M; Marques, V; Chaves, C; Silva, A; Cabral, H
Abstract: An ecosystem approach to fisheries management (EAFM) is as a new paradigm in fisheries management. In this study, a combination of geographic information systems (GISs) and multi-criteria decision-making method (MCDM) is proposed as a framework supporting an ecosystem approach to European sardine ( Sardina pilchardus, Clupeidae) fishery management in Portugal. This case study was chosen due to the recent severe decline shown by the species. To develop an EAFM for the sardine fishery, a set of criteria were defined based on literature review and expert knowledge. To address multiple conflicting objectives, namely conservation and fisheries, five scenarios were considered: (i) baseline ; (ii) nurseries protection ; (iii) spawning areas protection ; (iv) fishery profit driven, and (v) safeguarding dependent fishing communities . Combination of GIS and MCDM methods highlighted important areas to implement spatial conservation measures for sardine. The analyses indicate that some areas are suitable for conservation in several scenarios, such as the area near Aveiro and the area near the Tejo estuary. However, conservation measures implemented in the area near Aveiro would imply higher economic trade-offs when compared with the actions applied in the region near the Tejo estuary. Results also suggested some of the conservation objectives, such as the protection of sardine eggs and juveniles, to not be compatible. The proposed framework is an important tool supporting EAFM by addressing conflicting objectives, trade-offs and identifying areas that could be considered as potential fishery closure sites or subjected to further analyses.